1994
DOI: 10.1093/hmg/3.7.1053
|View full text |Cite
|
Sign up to set email alerts
|

Absence of the XIST gene from late-replicating isodicentric X chromosomes in leukaemia

Abstract: The mechanism of X-inactivation in man is thought to involve a specific cis-acting locus within the X-inactivation centre at Xq13 (1,2). The XIST gene (X inactive specific transcript) at Xq13 is ubiquitously expressed only from the inactive X and as such may be involved in or influenced by the X-inactivation process (3,4). We have localised the breakpoints on two acquired isodicentric X chromosomes associated with leukaemia to a 450 kilobase region of DNA within Xq13, which result in deletion of the XIST gene.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
44
0
3

Year Published

1996
1996
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 0 publications
3
44
0
3
Order By: Relevance
“…The role of XIST in the maintenance of repression has been questioned, however. Previous studies of inactive X chromosomes with XIST deletions indicate that XIST RNA is not necessary to maintain X inactivation (2,3), presumably because other repressive systems, such as promoter methylation, histone deacetylation, and͞or late replication, are maintaining inactivation. Our studies of human-hamster hybrids containing an inactive X chromosome with azacytidine-reactivated genes indicate that XIST expression is not sufficient to prevent reactivation or to reinitiate silencing of these genes (4).…”
mentioning
confidence: 97%
“…The role of XIST in the maintenance of repression has been questioned, however. Previous studies of inactive X chromosomes with XIST deletions indicate that XIST RNA is not necessary to maintain X inactivation (2,3), presumably because other repressive systems, such as promoter methylation, histone deacetylation, and͞or late replication, are maintaining inactivation. Our studies of human-hamster hybrids containing an inactive X chromosome with azacytidine-reactivated genes indicate that XIST expression is not sufficient to prevent reactivation or to reinitiate silencing of these genes (4).…”
mentioning
confidence: 97%
“…Although considerable attention has been focused on the relative timing and roles of these features during establishment of the Xi heterochromatic state early in development (26), once that epigenetic state is established, they have been widely considered to be redundant (27)(28)(29)(30)(31). One prediction of the epigenetic redundancy model is that the features of facultative heterochromatin should colocalize on the Xi in somatic cells.…”
mentioning
confidence: 99%
“…Recent studies, however, demonstrated that the XIST gene and the XIC are not strictly required for the maintenance of X inactivation in somatic hybrid cells (Brown and Willard, 1994) or in leukemic cells with a deleted XIST gene (Rack et al, 1994).…”
mentioning
confidence: 99%